Frequency of Retinopathy in Premature Infants in a Tertiary Care Hospital - Qureshi, Aamer Naseer; Riaz, Lubna; Nazeer, Shahid; Fatima, Sehar; Javed, Maria; Aamer, Mahnoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Retinopathy of prematurity is one of the important problems faced by neonates causing lifelong morbidity. It can be prevented by early detection and prompt treatment. Objective: To determine the frequency of retinopathy in premature infants in a Tertiary Care Hospital. Methodology: A three-centered cross-sectional study was conducted in tertiary care hospitals of Lahore. All neonates after taking informed consent form guardians were enrolled in the study according to selection criteria. All cases were screened for retinopathy of prematurity at four weeks of age for the first time and later followed up at 4 to 6 weeks interval according to disease stage on slit lamp by consultant ophthalmologist. The premature infants were diagnosed as retinopathy of prematurity based on the operational definition. Results: The mean age was 15.80±5.57 hours, mean gestational age of positive cases was 30.46±1.40 weeks and mean birth weight of positive cases was 1528.2.36±201.47 g. There were 15 (14%) cases who had retinopathy of prematurity while 96 (86%) cases had normal eyes. Among them 11 (73%) cases were of stage 1, 3 (20%) cases of stage 3 and 1(7%) case of stage 4 retinopathy of prematurity. Conclusions: In our study, retinopathy is observed in 14% of the premature infants.